2018
DOI: 10.1103/physrevd.97.104066
|View full text |Cite
|
Sign up to set email alerts
|

Gravitational-wave luminosity distance in modified gravity theories

Abstract: In modified gravity the propagation of gravitational waves (GWs) is in general different from that in general relativity. As a result, the luminosity distance for GWs can differ from that for electromagnetic signals, and is affected both by the dark energy equation of state wDE(z) and by a function δ(z) describing modified propagation. We show that the effect of modified propagation in general dominates over the effect of the dark energy equation of state, making it easier to distinguish a modified gravity mod… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
243
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 179 publications
(254 citation statements)
references
References 71 publications
(105 reference statements)
11
243
0
1
Order By: Relevance
“…for some function δ(η). This behavior has been first found explicitly in scalar-tensor theories of the Horndeski class [31,33,[35][36][37] and in nonlocal infrared modifications of gravity [19,20]. The analysis in [41] showed that also scalar-tensor theories of the DHOST type, as well as bigravity, display this phenomenon, so an equation of propagation of the form (5) is completely generic and appears in all the best studied models of modified gravity.…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…for some function δ(η). This behavior has been first found explicitly in scalar-tensor theories of the Horndeski class [31,33,[35][36][37] and in nonlocal infrared modifications of gravity [19,20]. The analysis in [41] showed that also scalar-tensor theories of the DHOST type, as well as bigravity, display this phenomenon, so an equation of propagation of the form (5) is completely generic and appears in all the best studied models of modified gravity.…”
Section: Introductionmentioning
confidence: 77%
“…In the context of standard General Relativity (GR), the coalescence of compact binaries provides another way of measuring d L , as was realized long ago [3] (see e.g. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] for a sample of the many developments of the idea), so these sources are referred to as "standard sirens", the GW analogue of standard candles. Together with a determination of the redshift (which is not provided by the gravitational signal and must be obtained from an electromagnetic counterpart or with statistical techniques), this allows us to use GW observations as probes of cosmology.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Let us then study first the general consequences of eq. (3.50) (we closely follow the discussion in [164,165]). We proceed as in the GR case, except that now, to eliminate the friction term, we must introduceχ A (η, k) from Then we getχ…”
Section: Tensor Perturbations In Modified Gravitymentioning
confidence: 89%
“…where d L (z) is the usual notion of luminosity distance (note that, since only the ratios a(z)/ã(0) and a(z)/a(0) enter, without loss of generality we can choose the normalizations a(0) = a(0) = 1). Equation (3.55) motivates the introduction of a 'GW luminosity distance' d gw L (z) [164], related to the standard luminosity distance appropriate for electromagnetic signals, that we henceforth denote by d em L (z), by d gw L (z) = [a(z)/ã(z)] d em L (z). Rewriting eq.…”
Section: Tensor Perturbations In Modified Gravitymentioning
confidence: 99%